La Campaña Nacional 1856-1857 y la construcción del Estado nación - Fallas, Carmen María (2016)
This article argues that in the decade of the 1850s the National Campaign prompted the nation state building process in Costa Rica. President Mora's and Bishop Monsignor Anselmo Llorente's proclamations calling to take arms in defense of fatherland, family, religion and properties contributed to awaken in the population the consciousness that they were pan of a unique and different community, and mobilized them to fight against those who threatened its independence. The welcome as heroes of the soldiers who returned victorious from the battles of Santa Rosa, Rivas and the San Juan river encouraged nationalism and increased the prestige of the military chiefs and the image of the army as representative of the interests of the society in general. With the National Campaign, as well, presidential authority was strengthened and legitimized by associating Mora with the defense of sovereignty.